Relationship between auditory discrimination of Serbian language phonemes and dysgraphia in different forms of written expression - Vesela Milankov; Ivana Anđić; Jelena Vrućinić; Ljiljana Simić; Milica Stelkić (Биомедицинска истраживања, 2021)
Introduction: Writing is the most complex human ability and the most direct form of communication. Auditory discrimination is the ability to distinguish different sounds of language. After the age of seven, difficulties in auditory discrimination, even of similar sounds, are considered a pathological phenomenon. The aim of the research was to determine whether difficulties in auditory discrimination of phonemes are related to the manifestation of dysgraphia in children of younger school age. Methods: The research was conducted at the Elementary School "Vuk Karadzić" in Priboj, during 2020, with the previous consent of the school principal, as well as the students' parents. The research sample included fifty children of the third and fourth grade, aged 9 and 10. For the purpose of this research, two tests were used: the Phonemic Discrimination Test (Kostić, Vladisavljević, Popović, 1983) and the Dysgraphic Handwriting Assessment Test (Ajuriaguerra, Auzias. 1971). Results: There was no significant difference in achievement in the Phonemic Discrimination Test between boys and girls. Half of the tested students achieved the maximum score in the Phonemic Discrimination Test and they were fairly equal in their achievement in the Phonemic Discrimination Test. Girls generally had harmoniously developed handwriting, while more than half of the boys in the categories had inconsistent handwriting or dysgraphic handwriting when it came to the forms of dictation, free topic and transcription. No statistically significant correlations were found between the results in the Phonemic Discrimination Test and the Dysgraphic Handwriting Assessment Test, p > 0.05. Conclusion: Based on the assessment of writing ability and auditory discrimination in young school children, no statistically significant association was found between auditory discrimination of sounds and manifestations of dysgraphic handwriting in all three forms of written expression (dictation, free topic, transcription).
Keywords: students; writing; auditory discrimination; dysgraphia